Kewenangan Jaksa Dalam Melakukan Penyadaoan Terhadap Setiap Orang Yang Berpotensi Melakukan Tindak Pidana Korupsi Di Bandar Lampung - I Ketut Seregig; Nur Amalia Zahra; Zainab Ompu Jainah (Penerbit Goodwood, 2025)
Purpose: This study aims to analyze the legal basis and limitations of the prosecutor’s authority to conduct wiretapping against parties potentially involved in corruption offenses, and to examine its implementation in the practice of corruption law enforcement.Research Methodology: This study employs a juridical-empirical approach. The research was conducted at the Bandar Lampung District Prosecutor’s Office. Data were collected through in-depth interviews with prosecutors and related law enforcement officers, supported by a review of laws and regulations, legal documents, and scholarly literature on prosecutorial authority, wiretapping, and corruption offenses.Results: The findings indicate that prosecutors in Indonesia do not have general or independent authority to conduct wiretapping. The Prosecutor’s Law does not explicitly regulate wiretapping authority for prosecutors. In practice, prosecutors do not carry out wiretapping directly, but only make use of wiretapping results lawfully obtained by authorized institutions, such as the Corruption Eradication Commission, in accordance with applicable legal procedures.Conclusions: This study is limited to law enforcement practice at the Bandar Lampung District Prosecutor’s Office and relies on interview data from a limited number of informants, so its findings do not fully represent the practice of wiretapping by prosecutors in other regions of Indonesia.Contribution: This study contributes to the development of criminal law and criminal procedure law by clarifying the limits of prosecutorial authority in wiretapping practices, and provides insights for policymakers and law enforcement agencies to strengthen legal certainty and human rights protection in corruption law enforcement.